Use of electronic health records to develop a more robust phenotype of pediatric overweight and obesity (Revista de Investigaciones Universidad del Quindío, 2023)
Clinical EHR data can be used to better develop a more robust phenotype of pediatric overweight and obesity.
Keywords: Overweight; obesity; electronic health record; eHealth; transdisciplinary; phenotype